Effect of water activity and temperature on growth of Alternaria alternata on a synthetic tomato medium - Pose, Graciela Noemi (2009)
Alternaria alternata is a toxigenic fungus, predominantly responsible for Blackmould of ripe tomato fruits, a disease frequently causing substantial losses of tomatoes, especially those used for canning. The objective of this study was to determine the effect of water activity (aw, 0.904, 0.922, 0.954, 0.982) and temperature (6, 15, 21 and 35 °C) on germination and radial growth rate on a synthetic tomato medium of a cocktail inoculum of five strains of A. alternata isolated from tomato fruits affected by Blackmould. The shortest germination time (1.5 days) was observed at 0.982 aw, both at 21 °C and 35 °C. The germination time increased with a reduction on aw. The fastest growth rate was registered at 0.982 aw and 21 °C (8.31 mm/day). Growth rates were higher when aw increased. No growth or germination was observed at the lowest aw level evaluated (0.904) after 100 days of incubation at 6 °C and 15 °C. A temperature of 6 °C caused a significant reduction in growth rates, even at the optimum aw level. The knowledge on the ecophysiology of the fungus in this substrate is necessary to elaborate future strategies to prevent its development and evaluate the consumer health risk.